REVEALING THE MEDICINAL SIGNIFICANCE, INNOVATIVE ASPECTS, CURRENT EXISTING CHALLENGES, AND PHARMACOLOGICAL ATTRIBUTES OF MURRAYA KOENIGI (The Research of Medical Science Review, 2025)
Murraya koenigii has been used as a traditional medicinal plant due to the presence of bioactive compounds makes them effective for therapeutic applications. It belongs to family Rutaceae and widely found in tropical and sub-tropical regions. It is commonly known as “Meethi Neem” or “Curry Tree” with small deciduous shrub reaching up to 2.5 to 6 meters of height. It is a rich source of bioactive compounds such as alkaloids, sesquiterpenes, flavonioids, koenine, β-sitosterol, carbazole, koenidine, koenidine, girinimbine, girinimbiol, and terpenes. It has been used in the treatment of various diseases such as piles, itching, inflammation, edema, dysentery, and fresh wounds. It also has high medicinal potentials such as antipyretic, anti-obesity, anticarcinogenic, antifungal, antibacterial, antioxidant, hypolipidemic, antihypertensive, larvicidal activities and hepatoprotective, gastroprotective, cardioprotective effects. Moreover, this plant had not any toxicological or adverse effects on the health. Therefore, it can be used for treatment a number of different infectious diseases. This review illustrated the medicinal significance, pharmacological applications, and novel therapeutic aspects of Murraya koenigii.